2000
DOI: 10.1017/s0021859699007728
|View full text |Cite
|
Sign up to set email alerts
|

Influence of additional ammonium supply on some nutritional aspects in hydroponic rose plants

Abstract: The influence of an additional supply of ammonium to a nitrate containing hydroponic solution on the mineral nutrition of greenhouse rose plants (Rosa hybrida cv. ‘Lambada’) has been investigated. The effect on NPK uptake, mineral contents in roots and leaves as well as nitrate reductase (NR) and glutamine synthetase (GS) activities were examined. The addition of ammonium in a nutrient solution containing nitrate produced a total nitrogen uptake increase during shoot elongation, while in the absence of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 7 publications
2
8
0
3
Order By: Relevance
“…The following nitrate assimilation is testified by the increments of this component in the treated samples, which can be attributed to the decrease of photosynthetic organic matrix. The phosphate contents decrease and, on the other hand, the increase in the nitrate content, observed in the three tests (Table 1), might be due to a response determined by the need for an equilibrium of cellular homeostasis (Gniazdowska and Rychter, 2000;Lorenzo et al, 2000). The variations of the reduced and oxidized forms of ascorbic acid (Table 2) are in agreement with the higher involvement registered for the APX activity in comparison with the PPO activity ( Table 3).…”
Section: Resultssupporting
confidence: 74%
“…The following nitrate assimilation is testified by the increments of this component in the treated samples, which can be attributed to the decrease of photosynthetic organic matrix. The phosphate contents decrease and, on the other hand, the increase in the nitrate content, observed in the three tests (Table 1), might be due to a response determined by the need for an equilibrium of cellular homeostasis (Gniazdowska and Rychter, 2000;Lorenzo et al, 2000). The variations of the reduced and oxidized forms of ascorbic acid (Table 2) are in agreement with the higher involvement registered for the APX activity in comparison with the PPO activity ( Table 3).…”
Section: Resultssupporting
confidence: 74%
“…High NH4+ concentrations significantly diminished the mean number of shoot per explant. This may be due to the significant inhibitory effects of NH4+ on other ionś uptake (Gerendás et al, 1997; Lorenzo et al, 2000). Moreover, some investigations suggested that high amounts of NH4+ adversely effect on plant metabolism causing to physiological and morphological disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of primary root growth by inhibiting cell elongation and division are toxicity symptoms as reported by Qin et al (2011) in Arabidopsis. A high ratio of ammonium to nitrate enhanced the uptake of P (Lorenzo et al 2000a) and N (Lorenzo et al 2000b) during shoot elongation by rose plants. This can be explained by the preferential uptake of NH 4 as compared with NO 3 (Marschner 1995), and also by the reduction of solution pH (Feigin et al 1986).…”
Section: Pot Experimentsmentioning
confidence: 95%